Interaction of seed treatment and herbicide tank mixture in paddy rice selectivity - Catoni, Julio Marcos; Oliveira Neto, Antonio Mendes de; Riscarolli, Cristiano; Guerra, Naiara (Revista de Ciências Agroveterinárias, 2020)
Increased phytointoxication level after herbicide tank mixtures has been frequent in field conditions, pressured by the improvement of the control spectrum and the advance of herbicide-resistant biotypes. The objective of this work was to assess the interaction of seed treatment with a commercial formulation of fungicide and insecticide with herbicide tank mixture after the application in paddy rice, in the pre-germinated seed system, in the Alto Vale do Itajaí region. To carry out the experiment in the commercial field prepared for the pre-germinated seed system, sowing SCS 121 CL cultivar. The experimental design was a block completely randomized with treatments organized in factorial design 4 x 2, with four replications. We assessed two levels seed treatment (with or without) and four herbicide treatments (without herbicide, [imazapyr + imazapic] + bentazon, [imazapyr + imazapic] + saflufenacil, and [imazapyr + imazapic] + bentazon + saflufenacil). The first spray was carried out in V2 only with the commercial mixture of [imazapyr + imazapic], and the second spray was carried out in V3 with treatments. The variables assessed were phytointoxication, number of plants per square meter, number of tillers by plant, number of panicles per square meter, number of grains per panicle, panicle weight, spikelet sterility, thousand grains weight, and grain yield. We concluded that seed treatment with a formulated mixture of insecticide and fungicide reduced the phytointoxication of saflufenacil mixing treatments. Moreover, there was numeric superiority of yield compounds and grain yield with seed treatment.